Nonoperative Treatment Versus Appendectomy for Acute Nonperforated Appendicitis in Children: Five-year Follow Up of a Randomized Controlled Pilot Trial. Issue 6 (June 2020) - Patkova, Barbora; Svenningsson, Anna; Almström, Markus; Eaton, Simon; Wester, Tomas; Svensson, Jan F.
Abstract : Objective: The aim of this study was to evaluate the safety and feasibility of nonoperative treatment of acute nonperforated appendicitis in children during 5 years of follow-up. Methods: A 4-year follow-up of a previous randomized controlled pilot trial, including 50 children with acute nonperforated appendicitis, was performed. The patients were initially randomized to nonoperative treatment with antibiotics or appendectomy with 1-year follow-up previously reported. Data were extracted from the computerized notes and telephone interviews. The primary outcome was treatment failure, defined as need for a secondary intervention under general anesthesia, related to the previous diagnosis of acute nonperforated appendicitis. Results: The children were followed up for at least 5 years [median 5.3 (range 5.0–5.6)] after inclusion. There were no failures in the appendectomy group (0/26) and 11 failures in the nonoperative group (11/24). Nine failures had occurred during the first year after inclusion, 2 of whom had histologically confirmed appendicitis. There were 2 further patients with recurrent acute appendicitis 1 to 5 years after inclusion. Both these patients had uncomplicated laparoscopic appendectomies for histologically confirmed acute appendicitis. There were no losses to follow-up. Conclusions: At 5 years of follow-up 46% of children treated with antibiotics for acute nonperforated appendicitis had undergone an appendectomy, although acute appendicitis was only histologically confirmed in 4/24 (17%). Treatment with antibiotics seems to be safe in the intermediate-term; none of the children previously treated nonoperatively re-presented with complicated appendicitis.